Fallen angel - Preminger, Otto; Preminger, Otto (20th Century Fox Home Entertainment, 2005)
June Mills and her sister Clara live a quiet life in a small costal town until Eric Stanton, a smooth-taking con man, comes into their lives. He seems to fall hard for June, but Clara believes he's interested only in the family fortune. Meanwhile, sultry waitress Stella catches Stanton's fancy and thinks he might be her ticket out of town. The local cop knows more than he's telling about his fellow citizens and their tangledd relationships, which draw even tighter after a shocking murder.